Contrastive Study on Differences in Sentence Aspects between Arabic, Tamil, and English Languages - Muhammadu Sainulabdeen, M.S. Zunoomy; Israth, U.; Aaqil, A.M.M. (LP2M IAIN Sultan Amai Gorontalo, 2022)
This research focuses on studying differences in sentence elements between Arabic, English, and Tamil by exposing similarities and dissimilarities. It uses a descriptive contrastive methodology. This research is based on a theory of linguistics. According to this, the researchers used books, articles, theses, and website articles to obtain the necessary information for Secondary data. It finds that Arabic, English, and Tamil belong to different linguistic families. The Arabic language belongs to the Semitic languages, no matter what, Tamil language belongs to Dravidian, and English belongs to the Indo-European family. In this case, they specialize in specific sentence elements according to their linguistic components. Based on this, there are more differences than similarities. For example, there are differences in gender, numeral, tense, pronouns, adjectives, genitives, and articles. These things affect learning a language as a foreign or second language. This study helps the learners to get the differences between the languages. Learners of Arabic, a foreign language, should pay attention to their own language grammar in order to be fluent in both languages to study the Arabic linguistic system in contrast to the Tamil language for learning a language in the best way and to learn Tamil language in the best way, regardless of their mother tongue to learn Arabic fluently.